Fragmenting labour: organisational restructuring, employment relations and the dynamics of national regulatory frameworks. (1st April 2010) - Jörg Flecker
Abstract : The conditions of work and employment are becoming increasingly diverse not only at global level, but also within countries, sectors and even organisations. The restructuring of companies and value chains contributes to this fragmentation of employment because restructuring is entangled with shifts in the forms of employment and the composition of labour. These tendencies, in turn, are shaped by specific national employment regulations which mediate both the employers' calculus underlying restructuring and the consequences of restructuring on labour. This paper draws on the results of two major EU-funded projects, WORKS and Dynamo, to present a range of different types of fragmentation of employment in the context of value chain restructuring, discusses their interplay with the institutional context and draws conclusions on national labour market regulations.